(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2021)
Companies seek to enhance investor confidence by achieving the highest level of transparency in disclosure of financial and non-financial information (SASB standards) for Iraqi insurance companies listed on the financial market. The aim of the research is to identify the extent of the ability of financial and non-financial information to enhance transparency in reporting, which is reflected in Investor confidence. And the standards of sustainability development accounting issued by (SASB) through the electronic questionnaire that was distributed. Companies seek to achieve a set of goals, the most important of which is to enhance investor confidence by improving transparency in disclosure. Concerning the employment of financial and non-financial information (SASB standards), the results were obtained by analyzing the results of individuals ’answers using the outputs of the SPSS program, as it was found that the disclosure of sustainability accounting standards (SASB standards) insurance standard (FNO301) and indicators of transparency in reporting issued by the institution (S&P) Contributes to enhancing investor confidence.